2023
DOI: 10.1186/s41747-023-00352-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined evaluation of blood flow and tissue perfusion in diabetic feet by intra-arterial dynamic 4DCT imaging

Abstract: Critical limb ischemia is associated with high mortality and major amputations. Intra-arterial digital subtraction angiography (IADSA) has been the reference standard but has some shortcomings including the two-dimensional projection and the lack of tissue perfusion information. The aim of this exploratory study is to examine four-dimensional computed tomography (4DCT) angiography and perfusion imaging using low-volume intra-arterial contrast injections for an improved anatomic and hemodynamic assessment in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…To our knowledge, perfusion in feet has not previously been quantified with PET, and only a few studies using MRI or CT have been published. Arterial spin labeling MRI appears to yield perfusion approximately 10 times higher than the current study in both lower legs and feet [ 20 22 ], whereas a small dynamic CT study in patients with diabetic foot found perfusion values more in line with the current study (0.5–0.7 mL/min/100 mL in healthy tissue of the feet) [ 23 ]. In both lower legs and feet, the interindividual variation was larger than the intraindividual variation in muscle perfusion (coefficient of variation 37% vs. 29% and 71% vs. 40%, respectively).…”
Section: Discussionsupporting
confidence: 61%
“…To our knowledge, perfusion in feet has not previously been quantified with PET, and only a few studies using MRI or CT have been published. Arterial spin labeling MRI appears to yield perfusion approximately 10 times higher than the current study in both lower legs and feet [ 20 22 ], whereas a small dynamic CT study in patients with diabetic foot found perfusion values more in line with the current study (0.5–0.7 mL/min/100 mL in healthy tissue of the feet) [ 23 ]. In both lower legs and feet, the interindividual variation was larger than the intraindividual variation in muscle perfusion (coefficient of variation 37% vs. 29% and 71% vs. 40%, respectively).…”
Section: Discussionsupporting
confidence: 61%